Metabolomic Profiling and Functional Characterization of Biochar from Vine Pruning Residues for Applications in Animal Feed - Serena Reggi; Sara Frazzini; Maria Claudia Torresani; Marianna Guagliano; Cinzia Cristiani; Salvatore Roberto Pilu; Martina Ghidoli; Luciana Rossi (Animals)
Biochar has gained interest as a feed ingredient in livestock nutrition due to its functional properties, circularity, potential to reduce environmental impact, and alignment with sustainable agro-zootechnical practices. The in vivo effects of biochar are closely tied to its physical characteristics, which vary depending on the biomass used as feedstock and the production process. This variability can result in heterogeneity among biochar types used in animal nutrition, leading to inconsistent outcomes. The aim of this study was to characterize the metabolomic and functional properties of an aqueous biochar extract from vine pruning waste, in order to predict its potential in vivo effects as a functional feed ingredient. A metabolomic analysis of the biochar extracts was conducted using quadrupole time-f-light (QQTOF) high-performance liquid chromatography tandem mass spectrometry (HPLC MS/MS). Antimicrobial activity against E. coli F18+ and E. coli F4+ was assessed using standard growth inhibition assays, while quorum sensing in E. coli exposed to biochar extracts was evaluated using real-time PCR. Prebiotic activity was assessed by exposing selected Lactobacillus strains to the biochar extract, monitoring growth patterns to determine species-specific responses. The metabolomic profile revealed several distinct molecular classes, including multiple peaks for phenolic compounds. The extract significantly inhibited the growth of both E. coli pathotypes, reducing growth by 29% and 16% for the F4+ and F18+, respectively (p < 0.001). The relative expression of the genes involved in quorum sensing (MotA, FliA for biofilm formation, and FtsE, HflX for cell division) indicated that the observed inhibitory effects likely resulted from interference with flagellar synthesis, motility, and reduced cell division. The biochar extract also showed species-specific prebiotic potential. In conclusion, biochar derived from vine pruning waste represents a valuable feed ingredient with functional properties that may help to reduce antibiotic use in livestock production.